Preservice Teachers’ Experiences in Experiential Instruction in Place Value - Ali, Clement Ayarebilla (Indonesian journal of science and mathematics education, 2023)
This study explored Kolb’s four-phase experiential learning cycle in the teaching and learning of place value at the University level. I deployed quasi-experimental pretest-posttest design with a sample of 42 preservice teachers who are undergoing education and training in the University to be become teachers. The first  21 received Kolb’s experiential model (experimental group) while the second 21 received traditional problem solving models as control group. In the tests, the performance of the preservice teachers in the experimental and control groups were compared using robust statistical t-test and ANCOVA analyses. The results showed that even though traditional Polya’s problem solving and scientific models were widely acknowledged, Kolb’s experiential principles of concrete experience, reflective observation, abstract conceptualization and active experimentation propelled  educational theory and practice into a new direction and focusing on much on the role that experience plays in the learning process. A follow up content analyses of four students’ sample work showed that Kolb’s experiential learning better developed their critical thinking and problem solving skills, effective communication skills, modern technology use, self-directions, and understanding in place value problems. Based on these findings, it is recommended that mathematics educators refocus and tailor their instructional techniques to Kolb’s experiential model of problem solving while bridging the gaps with the traditional problem solving strategies.